Protecting personal information in the era of identity theft: just how safe is our personal information from identity thieves? - Cassim, Fawzia (My University, 2015)
Identity theft has become one of the fastest growing white collar crimes in the world. It occurs when an individual's personal information such as inter alia his or her name, date of birth or credit card details is used by another individual to commit identity fraud. Identity theft can be committed via physical means or online. The increased use of the Internet for business and financial transactions, social networking and the storage of personal information has facilitated the work of identity thieves. Identity theft has an impact on the personal finances and emotional well-being of victims, and on the financial institutions and economies of countries. It presents challenges for law enforcement agencies and governments worldwide. This article examines how identity thieves use the personal information of individuals to commit identity fraud and theft, and looks at legislative solutions introduced in South Africa, the United States of America, the United Kingdom and India to combat identity theft crimes. The article examines measures introduced by the respective governments in these countries to counteract such crimes. Finally, the article will propose a way forward to counteract such crimes in the future. The study reveals that identity theft is a growing and evolving problem that requires a multi-faceted and multi-disciplinary approach by law enforcement agencies, businesses, individuals and collaboration between countries. It is advocated that businesses and institutions should take measures to protect personal information better and that individuals should be educated about their rights, and be vigilant and protect their personal information offline and in cyberspace.
Keywords: Identity theft; Fraud; Theft; Cybercrime; Personal information; Data; Internet; Cyberspace; Right to privacy; Computer users; Law enforcement agencies; Businesses; Legislation; South Africa; United States of America; United Kingdom; India